Exploring personal development and implications for leadership - Florio Zintel, Linda (Cranfield University, 2012)
In leadership development, an established literature and a fertile praxis fall short of clarifying how individuals may develop the many and varied capabilities that contribute to leadership processes. Literature promoting personal growth tends to reduce personal development to cognitive development or rely on broadly defined and under-evidenced notions. The adult development literature offers to this research a conceptualization of personal development as systemic qualitative change in individual sensemaking. As sensemaking develops, it progresses toward greater integration (of interdependent cognitive, emotive, purposive, and conative dimensions), sophistication, and self-determination. The research aimed to examine how changes in the sensemaking of individuals may result in developmental outcomes relevant for personal and leadership development. This inquiry moves from a perspective idealist ontology and a social constructivist epistemology, selects philosophical hermeneutics as a research paradigm, and embraces exploratory qualitative longitudinal research. Purposive sampling guided the selection of research context, a leadership program focused on personal growth. Transcripts from 32 semi-structured constructivist-phenomenological interviews, collected from nine participants across fourteen months, were analyzed through constructivist grounded theory. Development was assessed ipsatively according to a literature-based framework. Contributions, in terms of substantive theory, are not generalizable beyond research context and sample. This research advances the differentiation of developmental context, process and outcomes. Context is found to transcend holding environment—to be ideally conducive to a specific type of change in virtue of a distinctive emerging quality. While vector processes facilitate development, core processes (individual sensemaking) are development. In terms of outcomes, the research supports an association between personal development and development of leadership capabilities, but questions whether self-awareness or personality adjustments per se constitute authentic personal or leadership development. This research exposes a pattern of seeking affirmation, associated with disproportionate identity salience of external image, which is potentially capable of hindering personal development by triggering maladaptive rather than adaptive self-reflection.
Keywords: personal development; leadership development; authentic leadership development; affirmation; developmental context; developmental process; developmental outcomes; holding environment